Management of obesity: improvement of health-care training and systems for prevention and care. Issue 9986 (20th June 2015) - Dietz, William H; Baur, Louise A; Hall, Kevin; Puhl, Rebecca M; Taveras, Elsie M; Uauy, Ricardo; Kopelman, Peter
Summary: Although the caloric deficits achieved by increased awareness, policy, and environmental approaches have begun to achieve reductions in the prevalence of obesity in some countries, these approaches are insufficient to achieve weight loss in patients with severe obesity. Because the prevalence of obesity poses an enormous clinical burden, innovative treatment and care-delivery strategies are needed. Nonetheless, health professionals are poorly prepared to address obesity. In addition to biases and unfounded assumptions about patients with obesity, absence of training in behaviour-change strategies and scarce experience working within interprofessional teams impairs care of patients with obesity. Modalities available for the treatment of adult obesity include clinical counselling focused on diet, physical activity, and behaviour change, pharmacotherapy, and bariatric surgery. Few options, few published reports of treatment, and no large randomised trials are available for paediatric patients. Improved care for patients with obesity will need alignment of the intensity of therapy with the severity of disease and integration of therapy with environmental changes that reinforce clinical strategies. New treatment strategies, such as the use of technology and innovative means of health-care delivery that rely on health professionals other than physicians, represent promising options, particularly for patients with overweight and patients with mild to moderate obesity. The co-occurrence of undernutrition and obesity in low-income and middle-income countries poses unique challenges that might not be amenable to the same strategies as those that can be used in high-income countries.